KESENJANGAN ANTARA LANDASAN HUKUM DAN PRAKTIK PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - rizki, fino; Andriani, Opi; zamzami, mulki; ramadhani, nina wira (Program Studi Pendidikan Vokasi Seni Kuliner, 2024)
Providing all children, including those with special needs, the opportunity to learn together in the same classroom is the primary goal of inclusive education. Two regulations that support inclusive education in Indonesia are the Minister of National Education Regulation Number 70 of 2009 on Inclusive Education and Law Number 20 of 2003 on the National Education System. However, the policies and their actual implementation, especially in elementary schools, differ significantly. Several factors contribute to this discrepancy, including the lack of facilities to accommodate the needs of children with special needs, insufficient public awareness about the importance of inclusive education. The aim of this investigation is to identify practical solutions and examine the causes of this misalignment. As a conclusion to this study, a comprehensive approach involving the improvement of teacher competencies, the provision of adequate facilities, and the enhancement of public awareness is necessary to support the implementation of inclusive education in elementary schools.